Rediscovery of Impatiens parvifolia and reinstatement of I. omissa (Balsaminaceae) in India - Melesuparambil Anirudhan, Anitha; Mani, Bince; Gnanasekaran, Gunadayalan; Thomas, Sinjumol (Phytotaxa, 2023)
Impatiens parvifolia (Balsaminaceae) is recollected from the type locality and adjacent to the type locality after almost 160 years in addition to the resurrection of a less-known endemic species, I. omissa as a distinct species from the former based on detailed morphological study of type specimens deposited in different herbaria and fresh collections from the type locality. Further, the taxonomy of both species is discussed here with a detailed description, colour photographs, illustrations, and a taxonomic key showing distinguishing characters between these species.